The Young in the Kirchnerist Age (Argentina. 2007-2015): Political Payoff or Transformation Tool? - Becher, Yussef (2016)
The objective of this text (which also involves a working hypothesis) is to contribute elements intended to analyze social policies as political and institutional resources which can add to the building of a presidential leadership. Taking this as a starting point, social policies designed for the young—which were especially fostered and financed during Cristina Fernández de Kirchner‟s second term of office—are analyzed as elements that may have helped to build a political leadership. However, it is also appropriate to consider the presidency of Néstor Kirchner (2003-2007) in order to gain a better understanding of such a construction, since this is the point where the political-institutional scaffolding that propelled that leadership lies. With regard to social interventions of the young, different studies conducted across Argentina have highlighted the increase of social participation and citizenship building. Those studies provide some hints in relation to the question raised when considering such interventions as political and institutional resources: are the young a political payoff or a transformation tool?